Evaluation of the 235U prompt fission neutron spectrum including a detailed analysis of experimental data and improved model information - Neudecker Denise; Talou Patrick; Kahler Albert C.; White Morgan C.; Kawano Toshihiko (EPJ Web of Conferences, 2017)
We present an evaluation of the 235U prompt fission neutron spectrum (PFNS) induced by thermal to 20-MeV neutrons. Experimental data and associated covariances were analyzed in detail. The incident energy dependence of the PFNS was modeled with an extended Los Alamos model combined with the Hauser-Feshbach and the exciton models. These models describe prompt fission, pre-fission compound nucleus and pre-equilibrium neutron emissions. The evaluated PFNS agree well with the experimental data included in this evaluation, preliminary data of the LANL and LLNL Chi-Nu measurement and recent evaluations by Capote et al. and Rising et al. However, they are softer than the ENDF/B-VII.1 (VII.1) and JENDL-4.0 PFNS for incident neutron energies up to 2 MeV. Simulated effective multiplication factors keff of the Godiva and Flattop-25 critical assemblies are further from the measured keff if the current data are used within VII.1 compared to using only VII.1 data. However, if this work is used with ENDF/B-VIII.0β2 data, simulated values of keff agree well with the measured ones.